ISOLATION AND CHARACTERIZATION OF ALTERNARIOL AND ALTERNARIOL MONOMETHYL ETHER PRODUCED BY ALTERNARIA ALTERNATA OF GROUNDNUT - P. SUVARNALATHA DEVI,; M. N. REDDY,; S. D. S. MURTHY,; M. NAGALAKSHMI DEVAMMA,; P. JAYALAKSHMI,; G. REVATHI, (The Bioscan, 2010)
To study the patho-physiological role of Alternariol and Alternariol monomethyl ether in disease syndrome as well as their significance role in pathogenesis caused by Alternaria alternata (Fr.) keissler to Groundnut has been chemically characterized. The toxins Alternariol and Alternariol monomethyl ether identification was confirmed by Rf values on TLC in different solvent systems, UV and IR spectral analysis using authentic samples. The melting points 350ºC for AOH and 267ºC for AME were determined. It is believed that the present study would contribute not only to elucidate the role of toxins in plant parasite relationship but also to arrive an alternative concepts and strategies for plant protection.